Evaluating the level of sustainability of privately managed forest in Bogor, Indonesia - TATAN SUKWIKA; DUDUNG DARUSMAN; CECEP KUSMANA; DODIK RIDHO NURROCHMAT (Society for Indonesian Biodiversity, 2016)
Sukwika T, Darusman D, Kusmana C, Nurrochmad DR. 2016. Evaluating the level of sustainability of privately managed forest in Bogor, Indonesia. Biodiversitas 17: 241-248. This study discusses the sustainability of small scale private forest in Bogor, Indonesia. It aims to determine the dimensions of sustainable private-forest and analyzing the sustainability index of privately managed forest. This study uses multidimensional scaling (MDS) o analyze the dimensions of sustainability, ranked from 0 (the lowest) to 10 (the highest), along with the support of Rap-Pforest, in order to assess the level of similarity and dissimilarity for each dimension. Using this scale from the sustainability index, this study estimates the level of sustainability of each dimension. After measuring each attribute’s level of ordination RMS change on the X axis, we estimate the error’s effect using Monte Carlo analysis. This study shows that the ecology as well as legal and institutional dimensions are moderately sustainable, with a sustainability index of 53.66% and 52.48%. However, the dimensions of economy, socio-culture, as well as accessibility and technology are less sustainable, with an index measurement of 41.62%, 47.02% and 47.56%, respectively. Based on those five sustainability dimensions, this study concludes that in average the level of sustainability of private-forest management in the Bogor is not sustainable (48.47%). We recommend that to improve the sustainability of small scale private forest management in Bogor, multiple stakeholders should be involved to development the most appropriate policy options.